Prime Minister’s Decree No. 752 of the year 2022 on the Exclusion of some Regions, Entities and Dues from Being Subject to the Provisions of the Law Regulating the Use of Non-Cash Payment Methods Promulgated by Law No. 18 of the year 2019 = قرار رئيس مجلس الوزراء رقم 752 لسنة 2022 بشأن استثناء بعض المناطق والجهات والمستحقات من الخضوع لأحكام قانون تنظيم استخدام وسائل الدفع غير النقدى الصادر بالقانون رقم 18 لسنة 2019 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic